Aunt Dimity digs in - Atherton, Nancy (New York, N.Y., U.S.A. Viking, 1998)
A cozy mystery in an English village where a row has erupted over an archeological find. Some say it is genuine, others that it is a fake. Aided by the ghost of Aunt Dimity, sleuth Lori Shepherd investigates.
111936
Keywords: Kitchen, Peggy (Fictitious character); Dimity, Aunt (Fictitious character) -- Fiction; Women detectives -- England -- Cornwall (County) -- Fiction; Detectives -- England -- Cornwall (County) -- Fiction; Archeology -- England -- Fiction; Ghost stories; Cornwall (England : County) -- Fiction; England -- Cornwall (County); Detective and mystery stories; Mystery fiction